Neutralizing antibodies, new laboratory tests against SARS-CoV-2 - Figueroa Montes, Luis Edgardo (2022)
Introduction: in this review we will know the details of this new laboratory test, used to quantify neutralizing antibodies against SARS-CoV-2. This diagnostic test begins to have a greater role, due to the process of infection and vaccination in the world, to understand the mysteries of the correlate of immune protection. Content: neutralizing antibodies have the ability to block the ability of the virus to bind to the ACE2 receptor in human cells and these antibodies allow to eliminate the effect of invading microorganisms. Their activity is generated by proteins on the surface of viruses, which they bind to "block" infection. Neutralizing antibodies are defined in vitro by their ability to block the entry, fusion or exit of the coronavirus, that is, they are functional antibodies. Summary: Currently there are different laboratory tests (high-throughput immunoassay tests), which have the ability to detect immunoglobulin G anti-protein S antibodies to SARS-CoV-2 and which correlate with the gold standard laboratory tests for the determination of these antibodies. It is crucial that these high-throughput immunoassay tests are manufacturing validated against gold standard methods to determine the presence of neutralizing antibodies. Perspective: this review aims to expand the knowledge of this new test, which in the future will allow defining the immunological correlate values ​​generated by vaccines or by a previous infection.